Determination of spheres of forming and realization of competitive advantages of enterprises of chemical industry - Peteshova, Tetiana; Kasatkina, Maryna (Skhid, 2013)
In the articles investigational branch features of forming and realization of competitive edges of enterprises of nitric subindustry of chemical industry of Ukraine. The competition map of market of mineral fertilizers is worked out on a criterion «production volume» and level pyramid of descriptions of competitive edges of the investigated enterprises. Maintenance of every level of descriptions of pyramid is certain and reasons of loss of competition positions the investigated enterprises are indicated at the market.